Pengaruh Endoxan-Asta terhadap Pertumbuhan Embrio Ayam yang Disuntikkan pada Macam-macam Umur Pengeraman - Sri Sudarwati; Tien Wiati Suryono (Journal of Mathematical and Fundamental Sciences, 1978)
Abstract. The influence of Endoxan-Asta (cyclophosphamide) on the development of chicken embryos has been investigated by injecting the substance into the yolk sac of 2-,3-, 4-, 5-,6-, and 7-day old embryos. The 4- and 5-day old embryos were found to be the most affected by injecting 0,04 mg Endoxan per egg. The younger the embryo when Endoxan is administered, its influence of the development of long bones of the leg is shifted for the tarso-metatarsus to the tibio-tarsus (towards the bones which are situated more proximally). In all experiments done, ectopia viscerum is the most obvious malformation. It has been proven clearly, that Endoxan caused stunted growth.